The relation of the pleural thickening in tuberculosis pleurisy with the activity of adenosine deaminase - B. Uskul; H. Turker; C. Ulman; M. Ertugrul; A. Selvi; A. Kant; S. Arslan; M. Ozgel (Monaldi Archives for Chest Disease, 2005)
Selvi, A. Kant, S. Arslan, M. Ozgel. Background: Residual pleural thickening (RPT) still occurs in most patients with tuberculosis pleurisy despite advances in the treatment of tuberculosis. The aim of this study was to evaluate the significance of RPT in tuberculosis pleurisy with the patients clinical findings, biochemical and microbiological properties of pleural effusion and with the total adenosine deaminase (ADA) and isoenzymes levels. Methods: 121 tuberculosis pleurisy patients were evaluated retrospectively. According to posteroanterior chest x-rays, the 63 (52%) cases with the thickness 2 mm or more in lower lateral hemithorax were grouped as I and the 58 (48%) cases without pleural thickness were grouped as II. The amount of pleural effusion was classified into small, medium or massive according to their chest x-rays. In both groups; sex, age, symptoms score, bacteriological and biochemical tests and ADA levels were recorded. Results: 81 (67%) male and 40 (33%) female, overall 121 patients were enrolled into the study. RPT was found higher in males (p=0.014) and the increase ran parallel with the amount of cigarette smoking (p=0.014). RPT was found to be lower in small effusions (p=0.001). The group with RPT, the serum albumin was found lower (p=0.002), pleural fluid total protein (p=0.047) and the ratio of pleural fluid protein to serum protein (p=0.002) were found higher. In group I, total ADA: 69.5±38.9 IU/L and ADA2: 41.3±31.6 IU/L were higher than the cases without RPT (p=0.032, p=0.017, respectively). Conclusions: We suggest that the immunological mechanisms are effective in the development of pleural thickening.